2008
DOI: 10.1088/0953-8984/20/49/494213
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical and structural insights into the smectic phase of rod-like particles

Abstract: Abstract.Self-diffusion in a model system of rod-like particles is studied in the smectic (or lamellar) phase. The experimental system is formed by a colloidal suspension of filamentous fd virus particles, which allows the direct visualisation at the scale of the single particle of mass transport between the smectic layers. Self-diffusion takes place preferentially in the direction normal to the smectic layers and occurs in steps of one rod length, reminiscent of a hopping-type of transport. The probability de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 42 publications
4
54
0
Order By: Relevance
“…Due to the layered structure of the smectic-A phase, particles experience a periodic self-consistent molecular field perpendicular to the layers and therefore they mostly rattle around their position in a layer and occasionally jump from one layer to another. Because the layer-to-layer distance in this phase is about one particle length [33], this rattling and jumping motion presents itself as peaks in the self-part of the Van Hove function similar to those we observe in our simulations. The mechanism of the rattling and jumping motion that also presents itself in our simulations on the hexagonal phase is different from that in the smectic-A phase.…”
Section: Domain Size Effectssupporting
confidence: 84%
See 2 more Smart Citations
“…Due to the layered structure of the smectic-A phase, particles experience a periodic self-consistent molecular field perpendicular to the layers and therefore they mostly rattle around their position in a layer and occasionally jump from one layer to another. Because the layer-to-layer distance in this phase is about one particle length [33], this rattling and jumping motion presents itself as peaks in the self-part of the Van Hove function similar to those we observe in our simulations. The mechanism of the rattling and jumping motion that also presents itself in our simulations on the hexagonal phase is different from that in the smectic-A phase.…”
Section: Domain Size Effectssupporting
confidence: 84%
“…For the smallest system, peaks appear on the integer values of z/L where L is one particle length. This is similar to what has been observed in smectic-A phases formed by filamentous particles [7,33,37]. Due to the layered structure of the smectic-A phase, particles experience a periodic self-consistent molecular field perpendicular to the layers and therefore they mostly rattle around their position in a layer and occasionally jump from one layer to another.…”
Section: Domain Size Effectssupporting
confidence: 83%
See 1 more Smart Citation
“…Later, it was shown in a study based on dynamical density functional theory that this hopping-type diffusion is dictated by a temporary caging of particles by their direct neighbors that competes with the permanent self-consistent molecular field induced by all other particles. 30,31 A similar type of inter-layer diffusion was observed in the smectic phases of monodisperse rigid rod-like silica particles and in this case, in contrast to the above mentioned experiments involving semiflexible particles, layer-to-layer diffusion was slower than the in-layer diffusion. 32 This indicates that particle bending flexibility may enhance the inter-layer diffusion and/or it may slow down the in-layer diffusion.…”
Section: Introductionsupporting
confidence: 82%
“…27,28 The unusual self-diffusion of filamentous particles in the smectic-A phase has been the center of attention in computer simulations, theoretical studies and experiments. [29][30][31][32] Lettinga et al 29,30 studied the self-diffusion of individual particles in a suspension of semi-flexible fd virus at concentrations for which a smectic-A phase is stable. The authors observed a hopping-type diffusion, in which fd particles mostly rattle around their equilibrium positions in a smectic layer and occasionally jump from one layer to another.…”
Section: Introductionmentioning
confidence: 99%